Perceived social support, aggression, age and repeat offending as predictors of coping amongst male maximum-security offenders - Gwambe, Snethemba (University of the Free State, 2022)
This dissertation consists of five chapters. 𝗖𝗵𝗮𝗽𝘁𝗲𝗿 𝗢𝗻𝗲 introduces and orientates the reader to coping amongst incarcerated maximum-security offenders and emphasises the study’s problem statement, rationale/background, research aim, research questions, ethical considerations, and clarification of numerous concepts. Lastly, the value of the study is discussed. 𝗖𝗵𝗮𝗽𝘁𝗲𝗿 𝗧𝘄𝗼 provides the reader with an extensive literature review of coping amongst male maximum-security offenders and its related topics. 𝗖𝗵𝗮𝗽𝘁𝗲𝗿 𝗧𝗵𝗿𝗲𝗲 provides the reader with an outline of the study’s research methodology used to meet the research aim and answer the research questions. The research approach, research design, sampling procedure and data collection procedures will be discussed in this chapter. There will further be a discussion on the measuring instruments, data analysis procedures and ethical considerations of the study. 𝗖𝗵𝗮𝗽𝘁𝗲𝗿 𝗙𝗼𝘂𝗿 presents all the study’s research findings. Lastly, 𝗖𝗵𝗮𝗽𝘁𝗲𝗿 𝗙𝗶𝘃𝗲 encompasses a summary of the study’s findings. The value and contribution of the study will also be discussed, and chapter five will conclude with the limitations and recommendations for future research studies.
Dissertation(M.Soc.Sc.(Psychology))--University of the Free State, 2022
Keywords: Incarcerated maximum-security offenders; Coping; Male offenders